VCAM1 Promotes Tumor Cell Invasion and Metastasis by Inducing EMT and Transendothelial Migration in Colorectal Cancer - Zhang, Dan; Bi, Jiaxin; Liang, Qiaoyan; Wang, Shuyang; Zhang, Lingjie; Han, Fangyi; Li, Shengnan; Qiu, Bowen; Fan, Xingdi; Chen, Wei; Jiao, Hongli; Ye, Yaping; et al. (Frontiers in Oncology, 2020)
Vascular cell adhesion molecular 1 (VCAM1), an important member of the immunoglobulin superfamily, is related to the development of malignant tumors, such as breast cancer, melanoma, and renal clear cell carcinoma. However, the molecular role and mechanism of VCAM1 in the regulation of the progression of colorectal cancer (CRC) has rarely been studied. The results of IHC and RT‐PCR analyses proved that VCAM1 was upregulated in human CRC tissues compared with matched adjacent normal intestinal epithelial tissues. Moreover, analysis of data from the TCGA and Gene Expression Omnibus (GEO) databases revealed that a higher level of VCAM1 was strongly correlated with poor differentiation, metastasis and short survival in CRC patients. Furthermore, VCAM1 significantly influenced the invasion and metastasis of CRC cells in vitro and in vivo and activated the EMT program by which cancer cells adhere to the endothelium and cross the vessel wall by forming pseudopodia and invadopodia. The current findings demonstrate that VCAM1 promotes tumor progression in CRC.